Budget Institutions in G-20 Countries : An Update. (Policy Papers; Policy Paper ;, 2014)
The recent crisis left many G-20 countries with significant fiscal consolidation needs. There is evidence that well-designed budget institutions can help countries to plan and deliver successful fiscal adjustments. A 2010 internal IMF study identified ten budget institutions which can support the consolidation process, assessed their strength in each G-20 country, and identified priorities for institutional reform. Following consultations with all G-20 countries and using a revised evaluation framework, this paper: (i) reports on progress in strengthening their budget institutions; (ii) analyzes their impact on post-crisis fiscal performance; and (iii) makes recommendations for further institutional reform.